Conflict Resolution: Zakat Poverty Alleviation Solutions in West Java - Rifa Anggyana; Bunyamin Maftuh; Elly Malihah (UIN Sunan Gunung Djati Bandung, 2021)
Poverty is a problem faced by all nations, including Indonesia. Various kinds of policies have been made by the government to overcome this problem both in sectoral, monetary, fiscal, and other policies, but the policies have not been fully able to solve problems that occur in the field. The gap between theory and the field can be seen in the not yet implementing good zakat management. Conflict resolution to overcome this is necessary because Zakat is one of the important instruments in poverty alleviation. The more zakat that is collected and the more targeted it is in its distribution, the more it will be able to reduce existing poverty. Therefore, zakat has a crucial role in the growth of the economy and development. Seeing the fact that the potential for zakat has not been fully exploited in Indonesia, the government needs to make special policies to increase it. This research will discuss conflict resolution in terms of literature review to alleviate poverty in Indonesia, especially West Java.